PENGARUH METOE PQ4R TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PEREDARAN DARAH MANUSIA - Mauliana, Voni; Putri Panjaitan, Ruqiah Ganda; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purposed of this research is to find out the effect of PQ4R method on the students? learning outcomes in material of blood circulation system in human body in the eight grade of SMPN 3 Siantan. This research was quasi experimental design with nonequivalent control group design. Research samples were class VIII A as the experimental class and VIII B as the control class, with a saturated sampling as a sampling technique. The instrument was the multiple choice test with 20 questions. The average student learning outcomes in the experimental class was 15,41, while the control class was 14,18. The results of the t test analysis showed that tcount 2,28 > ttable 1,68, meaning that there were significant differences between the learning outcomes of students taught used PQ4R method and the learning outcomes of students taught used a lecture method. The effect size was 0,2324 with falling into the moderate category, having an effect of 23,24%.Keywords: PQ4R Method, Learning Outcome, Material of Blood Circulation System in Human Body